arab - Rabiatul Adawiyah; Abdul Qodir (Program Studi Pendidikan Bahasa Arab, 2024)
This research aims to describe the use of eclectic methods in learning Arabic at the Darul Falah Lima Jombang Islamic Boarding School. Arabic is taught only once a week at dawn using a mixed method (eclectic), which combines reading, writing and question and answer methods. This method is effective in improving students' learning abilities, stimulating enthusiasm for learning, reducing boredom, and preventing students from depending on just one method. This research uses a qualitative approach with a case study type, collecting data through observation, interviews and documentation. The analysis technique is carried out by reducing information, displaying data, and concluding research results, as well as applying source triangulation to achieve data validity. The research results show that 1) The process of implementing selective methods in teaching Arabic at the Darul Falah Lima Jombang Islamic Boarding School combines reading, writing and question and answer methods. The teacher delivers material through short dialogues about daily activities, asks students to listen and imitate, then presents reading text related to the dialogue. Students read the text silently for five minutes, then several students read it in front of the class. Students are also asked to write vocabulary from the text. The lesson ends with the teacher asking questions related to the reading text, which the students answer. 2). the application of eclectic methods helps students get excited about learning and improve their Arabic language skills. However, the obstacles faced include a lack of practice using new vocabulary, students being sleepy in class and the minimum number of hours studying Arabic is insufficient.